(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article discusses the theoretical and practical foundations of using the STEAM approach in teaching biology. The article examines in detail the relevance of this approach, methods that can be used in biology lessons, projectbased learning methods, and innovative solutions aimed at solving problems.